Dysregulation of BMP, Wnt, and Insulin Signaling in Fragile X Syndrome - Song, Chunzhu; Broadie, Kendal (Frontiers in Cell and Developmental Biology, 2022)
Drosophila models of neurological disease contribute tremendously to research progress due to the high conservation of human disease genes, the powerful and sophisticated genetic toolkit, and the rapid generation time. Fragile X syndrome (FXS) is the most prevalent heritable cause of intellectual disability and autism spectrum disorders, and the Drosophila FXS disease model has been critical for the genetic screening discovery of new intercellular secretion mechanisms. Here, we focus on roles of three major signaling pathways; BMP, Wnt and insulin-like peptides. We present Drosophila FXS model defects compared to mouse models in stem cells/embryos, the glutamatergic neuromuscular junction (NMJ) synapse model, and the developing adult brain. All three of these secreted signaling pathways are strikingly altered in FXS disease models, giving new mechanistic insights into impaired cellular outcomes and neurological phenotypes. Drosophila provides a powerful genetic screening platform to expand understanding of these secretory mechanisms and to test cellular roles in both peripheral and central nervous systems. The studies demonstrate the importance in exploring broad genetic interactions and unexpected regulatory mechanisms. We discuss a number of research avenues to pursue BMP, Wnt and insulin signaling in future FXS investigations and the development of potential therapeutics.